2021
DOI: 10.1186/s12916-021-02142-x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of P-tau/Aβ42 in the cerebrospinal fluid with blood microRNAs in Alzheimer’s disease

Abstract: Background The most common biomarkers of Alzheimer’s disease (AD) are amyloid β (Aβ) and tau, detected in cerebrospinal fluid (CSF) or with positron emission tomography imaging. However, these procedures are invasive and expensive, which hamper their availability to the general population. Here, we report a panel of microRNAs (miRNAs) in serum that can predict P-tau/Aβ42 in CSF and readily differentiate AD from other dementias, including vascular dementia (VaD), Parkinson disease dementia (PDD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 82 publications
1
9
0
Order By: Relevance
“…In this study, the hsa-miR-143-3p levels were found to be decreased in the hippocampus of individuals with AD compared with the controls. Consistent with these data, other studies showed that hsa-miR-143-3p was dramatically reduced in the serum of individuals with AD relative to the controls and provide a promising noninvasive biomarker for AD diagnosis [ 35 , 37 ]. In contrast, the hsa-miR-143-3p levels have been found to be increased in exosomes isolated from the serum of patients with AD compared with control subjects [ 34 ].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In this study, the hsa-miR-143-3p levels were found to be decreased in the hippocampus of individuals with AD compared with the controls. Consistent with these data, other studies showed that hsa-miR-143-3p was dramatically reduced in the serum of individuals with AD relative to the controls and provide a promising noninvasive biomarker for AD diagnosis [ 35 , 37 ]. In contrast, the hsa-miR-143-3p levels have been found to be increased in exosomes isolated from the serum of patients with AD compared with control subjects [ 34 ].…”
Section: Discussionsupporting
confidence: 68%
“…Our group recently showed that melatonin interacts with DAPK1 to inhibit protein expression, but a loss of melatonin might not be sufficient to augment the protein stabilization of DAPK1, which indicates that the expression of DAPK1 is modulated by multiple mechanisms, including miRNAs, in AD [ 14 , 21 ]. By employing a variety of miRNA online databases, we identified hsa-miR-143-3p as an attractive and novel biomarker for early AD diagnosis [ 34 , 35 , 36 , 37 ]. Through validation using dual-luciferase reporter assays, we provide the first demonstration showing that human DAPK1 is a direct target of hsa-miR-143-3p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Among them, 35 studies4,6,7,12-43 related to tau (Supplemental Digital Content 1, which demonstrates characteristics of studies used for analysis of CSF tau levels in DLB, http://links.lww.com/WAD/A401), and 14 studies4-7,12,14,20,22,23,27,39,40,42,44 related to α-synuclein (Supplemental Digital Content 2, which demonstrates characteristics of studies used for analysis of CSF α-synuclein levels in DLB, http://links.lww.com/WAD/A402) were included, and 12 studies overlapped with each other.…”
Section: Methodsmentioning
confidence: 99%
“…A panel of miRNAs including miR-143-3p is a promising substitute for the traditional measurement of p-tau/A β -42 in cerebrospinal fluid as an effective biomarker of AD (Ref. 95). Overexpression of miR-26a-5p suppressed tau phosphorylation and A β accumulation in the AD mice by targeting DYRK1A (Ref.…”
Section: Common Mirna Biomarkersmentioning
confidence: 99%